Knee joint kinematics during the landing phase of the double leg jump in athletes with chronic groin pain - Bruinders, Ernestine Valmare (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScPhysio)--Stellenbosch University, 2017.